PARADIGM IN AETIOLOGY AND MANAGEMENT OF ZYGOMATIC COMPLEX FRACTURES IN PAKISTAN - Abbas, Assad; Syed, Iffat Batool; Abbas, Hasnain; Abbas, Iram (Journal of Ayub Medical College Abbottabad, 2012)
Objective: The purpose of this study was to compare the outcome of wire osteosynthesis with bone plating in the management of zygomatic complex (ZMC) fractures. The rationale was to enable the oral and maxillofacial surgeon to select either of the treatment procedure with confidence. Methods: In this quasi experimental study, Sixty five patients of ZMC fractures were randomly allocated in groups of bone plating and wire osteosynthesis. This was done through envelope draw method. Three points fixation with either of the treatment modality was undertaken. Titanium bone plating or stain less steel wire osteosynthesis was carried out at frontozygomatic suture, infra orbital rim and at zygomaticomaxillary buttress. Results: In this quasi experimental study, three patients failed to follow up. There were 31 patients in each group. Infra orbital step defect was observed in one patient of wire osteosynthesis and two patients of bone plating. Mild facial deformity was observed in two patients of wire osteosynthesis while none in that of bone plating. Conclusion: There is insignificant difference of proportion of infra orbital step defect and facial deformity between wire osteosynthesis and bone plating. Keywords: Zygomatic complex fracture; wire osteosynthesis; titanium bone plating, infra orbital step defect; facial deformity; malar flattening